A Case Study on Implementing Modularity in Software Development. Issue 2 (3rd April 2017) - Sun, Hongyi; Ha, Waileung; Teh, Pei-Lee; Huang, Jianglin
ABSTRACT: In today's business world, firms are facing pressures to reduce costs, enhance productivity, and maintain quality in new product development. Past studies have provided evidence that modularity can enhance performance of new product development. However, real-life cases on how to implement the concept of modularity are limited. This article aims to propose a model for modularity implementation in the context of embedded software development. The model was applied in a software company in Hong Kong. Results from the case company provide evidence that the average reuse rate of software modules increased from 31% to 71% after the implementation, with productivity increasing by 258%, cost reducing by 70%, and quality increasing by 72%. The practical implications are finally discussed.